2016
DOI: 10.4244/eijy14m10_01
|View full text |Cite
|
Sign up to set email alerts
|

Delayed coverage of drug-eluting stents after interventional revascularisation of chronic total occlusions assessed by optical coherence tomography: the ALSTER-OCT-CTO registry

Abstract: A significantly delayed DES coverage after CTO-PCI was observed. Given the known increased rate of ST following CTO-PCI and the known association between delayed DES coverage and ST, OCT may aid in determining the optimal duration of dual antiplatelet therapy after CTO-PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…On the other hand, the thicker neointimal coverage of DES in truelumen in CTO lesions might lead to in-stent restenosis. Heeger et al reported that significantly delayed DES coverage after CTO-PCI was observed, but they did not evaluate whether DES was implanted in subintima or in true-lumen using IVUS or OCT [28]. In addition, their study used different type DESs while we used only EES.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the thicker neointimal coverage of DES in truelumen in CTO lesions might lead to in-stent restenosis. Heeger et al reported that significantly delayed DES coverage after CTO-PCI was observed, but they did not evaluate whether DES was implanted in subintima or in true-lumen using IVUS or OCT [28]. In addition, their study used different type DESs while we used only EES.…”
Section: Discussionmentioning
confidence: 99%
“…As recently described acquired data was analyzed at the LightLab Imaging OCT-offline workstation (OCT-system software B.0.1, LightLab) [13,14]. Image assessments were performed in every 5 th cross-section.…”
Section: Oct-imaging and Analysis At Follow-upmentioning
confidence: 99%
“…Frequency domain OCT-pullbacks were performed according to guidelines and obtained with the Ilumien system (St. Jude Medical, Saint Paul, USA) [13,14,20,21]. As recently described acquired data was analyzed at the LightLab Imaging OCT-offline workstation (OCT-system software B.0.1, LightLab) [13,14].…”
Section: Oct-imaging and Analysis At Follow-upmentioning
confidence: 99%
See 2 more Smart Citations